2003
DOI: 10.1021/bi020613j
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Rhodopsin Congenital Night Blindness Mutant T94I

Abstract: The Thr94 --> Ile mutation in the second transmembrane segment of rhodopsin has been reported to be associated with a congenital night blindness phenotype in a large Irish pedigree. Previously, two other known rhodopsin mutants that cause congenital night blindness, A292E and G90D, have been shown in vitro to constitutively activate the G protein transducin in the absence of a chromophore. The proposed mechanism of constitutive activation of these two mutants is an electrostatic disruption of the active site s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
71
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(85 citation statements)
references
References 34 publications
14
71
0
Order By: Relevance
“…Janz et al (51) In addition, congenital night blindness mutants that are characterized by an open conformation of the chromophorebinding site for nucleophiles have been identified. For example, T94I opsin folds properly and binds 11-cis-retinal to form pigment, but T94I Rho displays reduced thermal stability, has a long lived Meta II photostate, and shows highly increased reactivity toward NH 2 OH in the dark compared with WT Rho (54,55). In addition, it has been shown that T94I opsin is constitutively active (55).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Janz et al (51) In addition, congenital night blindness mutants that are characterized by an open conformation of the chromophorebinding site for nucleophiles have been identified. For example, T94I opsin folds properly and binds 11-cis-retinal to form pigment, but T94I Rho displays reduced thermal stability, has a long lived Meta II photostate, and shows highly increased reactivity toward NH 2 OH in the dark compared with WT Rho (54,55). In addition, it has been shown that T94I opsin is constitutively active (55).…”
Section: Discussionmentioning
confidence: 99%
“…For example, T94I opsin folds properly and binds 11-cis-retinal to form pigment, but T94I Rho displays reduced thermal stability, has a long lived Meta II photostate, and shows highly increased reactivity toward NH 2 OH in the dark compared with WT Rho (54,55). In addition, it has been shown that T94I opsin is constitutively active (55). The abnormal function of this Rho mutant is likely related to the decreased thermal stability and opsin constitutive activity without protein misfolding.…”
Section: Discussionmentioning
confidence: 99%
“…In cone visual cells, the light-independent G protein activation by the retinal-free protein acts to desensitize the cells by lowering their overall photosensitivity (30,31). Similarly, in rod visual cells, the constitutive G protein activity accompanying some rhodopsin mutants that exhibit faster retinal-Schiff base hydrolysis can cause night blindness by desensitization of the cells (53,59,64). If retinal-free mammalian melanopsins also inherently possess some level of constitutive G protein activity, the spontaneous Schiff base hydrolysis and retinal release could similarly act to desensitize ipRGCs.…”
Section: Dog Opn4mentioning
confidence: 99%
“…Photolysis of rhodopsin was carried out using a continuous wave argon ion laser directed into the sample compartment from above by a concave mirror that dispersed the beam evenly over the cuvette, with beam gating carried out with a manual shutter. Complete photoisomerization of rhodopsin and all mutants was achieved without significant heating in less than 1 s. Transducin activation assays were carried out as described previously (39).…”
Section: Gpcr Family Alignments-blastmentioning
confidence: 99%
“…In summary, our results suggest that ET is a reliable and highly efficient method for Transducin activation by wild-type (WT) and mutant opsins is shown in the presence and absence of 11-cis-retinal and light. Transducin activity was assayed using membranes from transfected COS cells as previously described (39): OE, in the absence of retinal; q, in the presence of retinal; and E, time course for the reaction in the presence of retinal after exposure to light (h ) for each mutant listed. Membrane amounts were selected to give the same light-dependent transducin activation kinetics; experiments with detergent-purified rhodopsins confirmed that the specific activities in the light were not measurably different for the mutants and wild-type (data not shown).…”
Section: Et Residues Cluster At Functional Sites Inmentioning
confidence: 99%